Tackling the Gender Gap in Mathematics with Active Learning Methodologies - Maria Laura Di Tommaso; Dalit Contini; Dalila De Rosa; Francesca Ferrara; Daniela Piazzalunga; Ornella Robutti (Institute of Labor Economics (IZA), 2021)
We implement a teaching methodology aimed at improving primary school children's mathematical skills. The methodology, grounded in active and cooperative learning, focuses on peer interaction, sharing of ideas, learning from mistakes, and problem solving. We evaluate the causal effect of the intervention on the gender gap in mathematics in Italy with a randomized controlled trial. The treatment significantly improves girls' math performance (0.14 s.d.), with no impact on boys, and reduces the math gender gap by more than 40%. The effect is stronger for girls with high pre-test scores.
Keywords: I21; I24; J16; C93; 330; gender gap; mathematics; school achievement; primary school; active learning; teaching methodologies; randomized controlled trial